2011
DOI: 10.1007/s11060-011-0764-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete regression of papillary tumor of the pineal region after radiation therapy: case report and review of the literature

Abstract: Papillary tumor of the pineal region (PTPR) is a rare neuroepithelial tumor that arises in the pineal region. The optimal treatment for PTPR remains controversial, as no definitive treatment strategy exists for this lesion. It is not clear whether aggressive surgical removal is superior to biopsy followed by radiotherapy. The majority of cases in the literature have undergone attempted gross total resection with a supracerebellar-infratentorial or a transcallosal-transventricular approach. In this report, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Similarly, a pineal region tumor initially treated empirically with upfront Gamma Knife SRS was controlled for 7 years before the patient developed symptomatic recurrence and underwent GTR, at which time pathologic diagnosis of PTPR was made (1). Other authors have reported complete resolution and no tumor recurrence at 2 years of follow-up with fractionated radiation alone, in the absence of definitive surgery, for biopsy-confirmed PTPR (14).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, a pineal region tumor initially treated empirically with upfront Gamma Knife SRS was controlled for 7 years before the patient developed symptomatic recurrence and underwent GTR, at which time pathologic diagnosis of PTPR was made (1). Other authors have reported complete resolution and no tumor recurrence at 2 years of follow-up with fractionated radiation alone, in the absence of definitive surgery, for biopsy-confirmed PTPR (14).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, tumor regression after radiotherapy [10,32] or even tumor disappearance [33] was observed. Whole brain irradiation, local radiotherapy, gamma knife surgery, stereotactic linac radiosurgery were all used with different protocols [32,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to recurrence after seven years, gross total resection was performed in this particular case [16]. In another reported case, radiation therapy after endoscopic biopsy and third ventriculostomy has resulted in complete tumor regression at 25 months [17]. …”
Section: Discussionmentioning
confidence: 99%